Construction of Loudspeaker Enclosure to Increase Loudspeaker Performance - Imam Try Wibowo Imam Try Wibwo; Agus Purwanto Agus Purwanto (Prodi Fisika, Departemen Pendidikan Fisika, 2016)
A study has been done to construct loudspeaker enclosure of bass-reflex baffle type, to characterize the modelling of loudspeaker enclosure of bass-reflex baffle type into the electrical circuit, and to investigate the frequency response of loudspeaker enclosure of bass-reflex baffle type with respect to the efficiency of loudspeaker performance. The method used to construct loudspeaker enclosure of bass-reflex baffle type was determining elements of loudspeaker enclosure of bass-reflex baffle type, modelling loudspeaker enclosure of bass-reflex baffle type into the electrical circuit, and determining the frequency response based on the analogues circuit. The method used to investigate the frequency response of loudspeaker enclosure of bass-reflex baffle type was making graph of the frequency response using ORIGIN50 software. The results of construction of loudspeaker enclosure was the bass-reflex baffle with volume of the box (30x30x50) cm3 using loudspeaker woofer of CURVE brand with diameter of 10 inches and wood of MDF with thickness of 12 mm. The results of characterizing the modelling of loudspeaker enclosure of bass-reflex baffle type were as follows: the inductance was (0.373 0.003) mH, the electrical resistance was 6 , the mass of diafragm and voice coil was (20.04 0.01) g, the mechanical damping was (2.82 0.02) Ns/m, the compliance was (4.8 0.2)10-4 Nm, the air particle acoustical mass vibrated by diafragm was (0.3 0.1)102 kg/m4, the acoustical resistance in front and rear of diafragm was (2.2 0.4) Ns/m5, the acoustical capasitance of the box was (2.82 0.07)10-7 m5/N, the acoustical mass of the box was (2.27 0.01) kg/m4, the acoustical mass of the port was (0.3 0.1)102 kg/m4, the acoustical resistance of the port was (1.1 0.5)102 Ns/m5, the acoustical mass in front of the port was (4.92 0.04) kg/m4, the acoustical resistance in front of the port was (2.2 0.4) Ns/m5 and showed that the frequency response was similar to a lowpass filter with working region at the frequency range of (65-220) Hz. The results of measurement of the frequency response of the bass-reflex baffle showed that the frequency response was similar to a lowpass filter with working region at the frequency range of (69.98-199.18) Hz and showed that woofer loudspeaker performance could be more efficient.Keyword: loudspeaker, woofer, enclosure, bass-reflex baffle, element, analogy, frequency response, MDF